Volume 4A: Combustion, Fuels and Emissions 2015
DOI: 10.1115/gt2015-42596
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Flame Dynamics at Stable and Near-LBO Conditions for Swirl-Stabilized Kerosene Spray Combustion

Abstract: An experimental investigation was conducted to characterize the flame structures and dynamics at stable and near-lean blowout (LBO) conditions. The current experiments were carried out using a laboratory-scale aero-combustor with an internally-staged dome. The internally-staged injector consisted of pilot and main swirlers, and the pilot swirler was fueled with Chinese kerosene RP-3 while the main injector was chocked. The resulting spray flame was confined within a quartz tube under atmosphere pressure. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the past, various aspects of spray combustion were studied using laboratory scale model combustors with prefilming airblast atomisers, more or less similar to the one used in this study. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] The majority of the investigations used kerosene or a kerosene surrogate as a fuel. To the authors' knowledge, the influence of different single component hydrocarbon fuels on airblast atomised swirling spray flames, has not been investigated in detail.…”
Section: Lean Blowout and Fuel Influencementioning
confidence: 99%
See 1 more Smart Citation
“…In the past, various aspects of spray combustion were studied using laboratory scale model combustors with prefilming airblast atomisers, more or less similar to the one used in this study. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] The majority of the investigations used kerosene or a kerosene surrogate as a fuel. To the authors' knowledge, the influence of different single component hydrocarbon fuels on airblast atomised swirling spray flames, has not been investigated in detail.…”
Section: Lean Blowout and Fuel Influencementioning
confidence: 99%
“…Yang et al 44 found atomisation performance of their pilot spray to dominate the lean blowout process. Regarding flame dynamics, Zhang et al 18 indentified several fluctuation modes of the pilot flame of a staged injector at near lean blowout conditions with the axial oscillation being the most dominant mode. The specific influence of different liquid fuels on lean blowout of swirl-stabilised spray flames has been investigated by Burger et al 45,46 From their tests with a laboratory scale swirl-stabilised spray flame they concluded that lean blowout limits are potentially influenced by both physical and chemical fuel properties.…”
Section: Lean Blowout and Fuel Influencementioning
confidence: 99%
“…However, only a few fundamental studies focused on the ignition and combustion performance of RP-3 spray. Zhang et al [23] investigated the ignition limit of RP-3 spray at both stable and near-lean blowout conditions. They found that the rotation mode in the swirl flame is primary under stable conditions, while three modes of the flame dynamics, including vibration, rotation, and flame shedding, can be found at near-lean blowout conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al 14 experimentally investigated the ignition and LBO performance of a fuel-staged multi-injection combustor by comparing two different pilot atomizer designs, and the results showed that matching the pilot spray with swirling air streams was an effective method to improve stable combustion of the pilot stage. Zhang et al 15 analyzed the flame dynamics in a lean staged injector and concluded that the swirl-stabilized flame at near-LBO conditions consisted of three parts: axial oscillation mode, circumferential rotation mode, and flame shedding mode, and the axial oscillation mode took over the circumferential rotation mode when transitioning from stable to near-LBO flames.…”
Section: Introductionmentioning
confidence: 99%